ANALISIS POSITIONINGLAYANAN BCA CABANG KUTA - Amen Wirajaya; I Putu Gede Sukaatmadja; Abdullah Jawas (Faculty of Economics and Business Udayana University, 2013)
The aims of this study are investigating PT Bank Central Asia, Tbk. Kuta Branch positioning to its competitor in Bali;and superiority services of PT Bank Central Asia, Tbk. Kuta Branch based on customer perception and determining the best relevant marketing strategy for PT Bank Central Asia, Tbk. Kuta Branch to counter its competitor. The data will be analyzed using statistical method of Multi Dimensional Scaling and Correspondence analysis. The result of this study shows that BCA Kuta has similiarities with Mandiri, it means that Mandiri is the nearest competitor of BCA Kuta. BCA is superior in waiting time of teller services, ATM services, internet banking, and mobile banking.